2020
DOI: 10.3390/pr8030364
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Exergy Based Optimization and Control

Abstract: This work presents a critical review of the use of exergy based control and optimization for efficiency improvements in energy networks, with a background of exergy based analysis given for context. Over the past three decades, a number of studies using exergy were conducted to gain a performance advantage for high energy consumption systems and networks. Due to their complexity and the increased scale of the systems, the opportunity to misuse energy inevitability leads to inefficient operations. The studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…When the exergy analysis of the drying process was carried out, the exergy of the drying medium and grain was expressed in the form of exergy rate according to the basic state parameters [ 20 ]: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the exergy analysis of the drying process was carried out, the exergy of the drying medium and grain was expressed in the form of exergy rate according to the basic state parameters [ 20 ]: …”
Section: Methodsmentioning
confidence: 99%
“…Zohrabi et al [ 19 ] studied the exergetic performance of a pilot-scale convective dryer with exhaust air recirculation by a wood-chip drying experiment, and found that increasing the drying temperature, air volume flow rate, and recycling fraction improved the overall functional exergetic efficiency of the drying system, while exhaust air recirculation profoundly improved the overall functional exergetic efficiency of the drying system. Exergy analysis has been an important analytical method for scholars seeking to optimize control and improve the energy efficiency of drying systems over the past three decades [ 20 , 21 ]. Because the energy consumption index is jointly determined by dryer performance and drying process optimization, for some grain-drying systems the optimization of the drying process plays an important role in the evaluation of the energy-saving index.…”
Section: Introductionmentioning
confidence: 99%
“…For calculating the cost per exergy unit, the exergo-economic balance of each component should be obtained according to Equations (12) and (13) where c i is the cost of the streams, . C P is the cost rate of the equipment, .…”
Section: Definition Equationmentioning
confidence: 99%
“…However, this analysis alone fails to identify the quality of the dissipated energy and how much work potential is available. To assess both the quantity and the quality of the lost or gained energy, both the first and second laws of thermodynamics (SLT) must be used in conjunction with each other to provide a more thorough understanding of the conversion inefficiencies, termed exergy, James et al [13]. Exergy (Ex) is defined as the maximum theoretical work that a system can achieve when it comes into equilibrium with the environment or the dead state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation